2013
DOI: 10.1016/j.ijsu.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin; a diagnostic marker for appendicitis

Abstract: Our findings confirm that hyperbilirubinaemia has a high specificity for distinguishing acute appendicitis, especially when perforated, from other causes of RIF pain, particularly those not requiring surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
5
37
2
1
Order By: Relevance
“…Third, we found that no individual pathological test can rival CT in detecting acute appendicitis. Furthermore, contrary to previously suggested, LFT and lipase exhibit no correlations with acute appendicitis 19. On the other hand, we found that the combined abnormal results of WCC or CRP can achieve sensitivity comparable with a CT scan, as tables 2 and 5 illustrated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Third, we found that no individual pathological test can rival CT in detecting acute appendicitis. Furthermore, contrary to previously suggested, LFT and lipase exhibit no correlations with acute appendicitis 19. On the other hand, we found that the combined abnormal results of WCC or CRP can achieve sensitivity comparable with a CT scan, as tables 2 and 5 illustrated.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is contradictory to the suggestions of some previous studies 4 11 12 19 31. Furthermore, in the female >40 years old subgroup, no tests or combinations of tests successfully rejected the null hypothesis; this is likely a consequence of the small subset sample size (N=37).…”
Section: Discussioncontrasting
confidence: 92%
“…Although the comparisons of CRP, and total bilirubin levels between negative and positive appendectomy cases did not reveal statistical significance (p > 0.05), these parameters were significantly higher in the gangrenous/perforated appendicitis group than the other two groups of patients (p < 0.01, and p < 0.01, respectively Despite numerous studies evaluating the predictive role of total bilirubin levels for acute appendicitis cases [19][20][21][22][23][24][25], no studies investigating the significance of direct and indirect bilirubin levels for this subject have been detected in the literature so far. The assessment of direct bilirubin levels, which is considered to represent the novelty of our study, revealed significantly elevated values in patients with either acute non-complicated, or gangrenous/perforated appendicitis (p < 0.01).…”
Section: Discussionmentioning
confidence: 93%
“…D'Souza et al concluded that hyperbilirubinemia was associated with complicated appendicitis, and that elevated bilirubin levels had a higher specifity (82 %) than both WBC (34 %) and CRP (21 %), but a lower sensitivity (70 %, 80 %, and 95 %, respectively) for perforated appendicitis versus simple appendicitis (p < 0.01) [21]. In the present study, WBC count, NEU count, and NEU% were detected to be significantly higher in cases of acute appendicitis when compared to cases having undergone negative appendectomies revealing the diagnostic sensitivity of these parameters (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…There is a reasonable body of evidence to suggest that leaving a macroscopically normal Our regression analysis identified a number of factors associated with normal appendicectomy, which have also been identified by others, including age, female sex, white cell count, C-reactive protein and serum bilirubin. 7,[14][15][16] It is likely that surgeons do not take this full range of parameters into account when confronted with the decision to remove a normal appendix. One study proposed a standardised decision making tool based on the macroscopic appearance of the appendix.…”
Section: Discussionmentioning
confidence: 99%